Amorphous MoSx developed on Co(OH)2 nanosheets generating efficient oxygen evolution catalysts. Issue 44 (30th October 2017) - Sun, Fengzhan; Li, Changqing; Li, Bo; Lin, Yuqing
Abstract : aMoS x /Co(OH)2 nanosheets were synthesized by forming amorphous MoS x on Co(OH)2 nanosheets. The aMoS x /Co(OH)2 nanosheets demonstrate excellent OER catalytic activity with only 350 mV at 10 mA cm −2 . The incorporation of amorphous molybdenum sulfide enhances the hydrophilicity, favoring the availability of reactant, and induces electron transfer for enhancing the OER catalytic activity of Co(OH)2 . Abstract : Exploration of high-efficiency and inexpensive electrocatalysts for the oxygen evolution reaction (OER) is of great importance for the design of renewable energy storage and conversion devices. Herein, we prepared amorphous MoS x -encapsulated Co(OH)2 nanosheets (aMoS x /Co(OH)2 NSs) as strongly robust and active OER electrocatalysts via a three-step procedure: first, Co(OH)2 nanosheets with catalytically active octahedral MO6 structures were synthesized by the hydrothermal process; second, violent ultrasonication was applied to exfoliate individual nanosheets from stacked Co(OH)2 sheets and break them down into smaller sheets and attach MoS4 2− ions uniformly on the nanosheets; third, MoS4 2− ions were thermally decomposed into amorphous MoS x on the Co(OH)2 nanosheets. The role of the incorporation of the amorphous MoS x nanostructure was to enhance the surface hydrophilicity for the availability of H2 O and accelerate the electron transport capability for kinetic activities. Furthermore, the interaction between MoS x and Co(OH)2 is proposed to induce electron transfer from amorphous MoS x to Co(OH)2, which will promote the basic environment for cobalt sites, break the Co–O bond, favor the release of O2 molecules, and thus enhance the OER process. Optimization of the Co/Mo molar ratio demonstrated that aMoS x /Co(OH)2 NSs with the Co/Mo molar ratio of 8 had the best OER activity and delivered the overpotential of 350 mV at the current density of 10 mA cm −2 and the Tafel slope of 65.4 mV dec −1 in 0.1 M KOH. This study enriches the research on non-first-row (3d) metal incorporation for high-efficient OER catalysts and offers an alternative to noble metal catalysts.